INFLIXIMAB FOR REFRACTORY NEUROSARCOIDOSIS. (29th November 2012) - Viegas, S; Donnelly, A; Jones, B; Nicholas, R; Malik, O
Abstract : Neurological involvement is seen in 5–15% of sarcoidosis patients typically with involvement of the central nervous system. Standard treatment includes corticosteroids and other 'steroid sparing' immunosuppressive drugs. More recently refractory cases have been treated with the monoclonal anti-TNFa agent, Infliximab, with good effect as reported in the literature. We describe eight patients who have received such treatment. There were three men and five women, and of these four patients already had an established diagnosis of systemic sarcoidosis. Five patients had cord involvement and three patients had brain involvement at the onset of their neurological syndrome. Previous treatments included Prednisolone, Methotrexate, Azathioprine, Cyclosporin and Mycophenolate Mofetil. A standard regime was employed and administered at weeks 0, 2 and 6. Further doses were administered at 8 weekly intervals if necessary. Significant complications encountered were staphylococcal bacteremia (n=1) and reactivation of latent mycobacterium tuberculosis (n=1), although both patients were also on other immunosuppressive drugs at the time. Two patients developed an allergic reaction to Infliximab, requiring it to be discontinued. Overall, clinically significant progression, with worsening radiological appearances was observed in one patient only. No significant clinical deterioration was observed in the other patients, with either stabilisation or subjective improvement in the symptoms reported. No radiological progression was seen in these cases.